2018
DOI: 10.1007/s11242-018-1182-3
|View full text |Cite
|
Sign up to set email alerts
|

A Hygro-Thermo-Mechanical Multiphase Model for Long-Term Water Absorption into Air-Entrained Concrete

Abstract: Many concrete structures located in cold climates and in contact with free water are cast with air-entrained concrete. The presence of air pores significantly affects the absorption of water into the concrete, and it may take decades before these are fully saturated. This generally improves the long-term performance of such structures and in particular their frost resistance. To study the long-term moisture conditions in air-entrained concrete, a hygrothermo-mechanical multiphase model is presented, where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…While the work in [10] [24] derived a multi-phase (i.e., solid, liquid, gas) transport and mechanics model to assess the entire saturation curve for air-entrained cementitious materials. Until the idealized specimen arrived at its value of matrix saturation, Sm, the model follows a similar imbibition study found in [23].…”
Section: -Theoretical Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…While the work in [10] [24] derived a multi-phase (i.e., solid, liquid, gas) transport and mechanics model to assess the entire saturation curve for air-entrained cementitious materials. Until the idealized specimen arrived at its value of matrix saturation, Sm, the model follows a similar imbibition study found in [23].…”
Section: -Theoretical Modelingmentioning
confidence: 99%
“…The approach has been adopted by AASHTO [9]. Additionally, based on the assumptions presented and found in [8,10,24], recent efforts have shown how a simple geometric model can be used to predict the evolution in Powers' spacing factor [27,28] between remaining air-filled voids, as more and more air voids become water-saturated [25]. The presented efforts have provided significant insight and advancement with respect to how airentrained cementitious materials may become increasingly saturated.…”
Section: -Theoretical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Other notable theories, including osmotic pressure, critical saturation, crystallization pressure, and microlens theories, have also been proposed to model the damage sustained during freeze–thaw cycles . Adjacent air-entrained voids can lessen the pressure of trapped water and ice in the capillary pores and reduce the damage to the microstructure, as well as reduce the overall degree of saturation of the concrete. , While the porosity of entrained air voids is important, parameters including void size distribution and spacing are also very influential on the freeze–thaw performance . Entrained air voids are usually between 0.01 to 1 mm in size and primarily near-spherical.…”
Section: Introductionmentioning
confidence: 99%